Areal features in northern sub-Saharan Africa: introduction - (:unkn) unknown (My University, 2015)
In this introductory paper for the workshop on areal phenomena in northern sub-Saharan Africa, we will focus on progress in the identification and explanation of areal features since Güldemann (2008) and Clements & Rialland (2008). On the one hand, we will add a diachronic perspective to some of the known features, such as the predominance of clause-final negation and the presence of labial-velars. We will show that the former is due to the presence in the languages of the area of a more general grammatical category of clause-final markers whose core function is the expression of intersubjective meanings, combined with a tendency for negative markers to grammaticalise from such kind of intersubjective markers, since negation is typically one of the situations where the speaker’s assertive authority is at stake. For the latter, we will point out meaningful differences in frequency and phonotactic distribution of labial-velar stops within the area. Thus, labial-velar stops tend to be restricted to stem-initial position and show a preference for the following vowel to be low and non-front, which is indicative of their historical sources and the factors that are responsible for their frequent emergence in the languages of the area. In addition, although labial-velars are found throughout northern sub-Saharan Africa, there appear to be three zones where their frequency within the lexicon is particularly high, viz. a coastal area from Sierra-Leone to the Cameroon border, some Ubangian languages in Central Africa, and Moru-Mangbetu languages in the north-east of the DRC. Arguably, these three zones are local labial-velar hotbeds.On the other hand, we will identify a number of additional candidate areal features, some of which are not easy to retrieve from descriptive grammars. Thus, we will present our first findings on stem-initial consonant length in a number of north-western Bantu languages, showing with instrumental data that stem-initial conso
Keywords: African Research